Intussusception secondary to a solitary peritoneal lung metastasis. (22nd April 2013) - Wou, C; Sharp, E; Johnson, L
Abstract : We report a 77-year-old woman, newly diagnosed with a malignant lung neoplasm of indeterminate nature who presented with profuse bilious vomiting without abdominal distension, pain or constipation. CT confirmed proximal small bowel obstruction. Laparotomy found a large area of intussusception from an intraluminal mass in the small bowel, which was resected and a primary anastomosis performed. Histology reported the mass as metastatic non-small-cell carcinoma and brought clarity to the primary tumour diagnosis. The patient made a good recovery from the operation, but unfortunately died a few months later from complications of her metastatic disease.